Understanding Digital Image Processing in Object Identification Against the Development of Information Technology - Saptha Negoro, Wahyu; Hendra Azhar, Asbon; Adinda Destari, Ratih; Soeheri (Universitas Putra Indonesia YPTK Padang, 2025)
Digital image processing is one of the important branches of computer science that plays a major role in supporting accurate and efficient object identification. This service aims to analyze the extent to which understanding the concepts and techniques of digital image processing can contribute to the progress of object identification, especially in the context of the increasingly rapid development of information technology. By using a descriptive-qualitative approach and literature study, this service uses various image processing methods such as segmentation, edge detection, and machine learning-based classification and others. The data used in this service is secondary data as an implementation of the object process in digital image processing for students' understanding of object detection. The results show that a deep understanding of image processing not only improves the accuracy of object identification, but also opens up opportunities for application development in various fields such as security, health, agriculture, and the manufacturing industry and this service can provide education for students to learn about the development of information technology in digital images. Thus, digital image processing is an important component in supporting digital transformation and information technology innovation in the future.